Intensitas Kebisingan Berdasarkan Jenis Tipe Pesawat Terbang Di Bandar Udara Internasional Minangkabau, Padang Pariaman, Sumatera Barat - Luthfi Fahreza; Melati Ferianita Fachrul; Asih Wijayanti (Journal of Environmental Engineering and Waste Management, 2019)
The purpose of this research is to study the challenges thar exist in the Minangkabau International Airport, Padang Pariaman, West Sumatera and  surrounding settlements. Find out how to fly at aiports. The primary data collection method is carried out using a Sound Level Meter, to measure aircraft compability when taking off and landing at 16 points in April – May 2018. The measurement point is determined based on ICAO (International Civil Aviation Organization) The results of the study show the facts above. Point 4 with a distance of 1000 meters from the end of the runway and has an intensity of 97.9 dB(A) and point 5 as far 2000 meters located at the airport which has a resolution level of 89.5 dB(A), according to Minister of Transportation Decree No. 48/2002 Point 4, a distance of 1000 meters from noise sources is included in the level III area. Based on the results obtained from the highest level in the regional area produced by Boeing 737-800 aircraft at 97.9 dB(A) and lower flying intensity at Point 3 at 61.7 dB (A. Suggestions given about others need to be improved with further assistance, special agreements were made on how to create a barrier or building installation damper such as planting more trees attached to the wall.